CO2 sequestration in basaltic rocks in Iceland: Development of a piston-type downhole sampler for CO2 rich fluids and tracers - Alfredsson, H.; Wolff-Boenisch, Domenik; Stefansson, A. (Elsevier BV, 2011)
The reduction of atmospheric CO2 is one of the challenges that scientists face today. University of Iceland, Reykjavik Energy, CNRS in Toulouse and Columbia University have started a cooperative project called CarbFix (www.carbfix.com) aiming at CO2 mineral sequestration into basalts at Hellisheidi, SW Iceland. Gaseous CO2 will be injected into a borehole where it will be carbonated with Icelandic groundwater. The CO2 charged injection fluid will be released into the target aquifer at ca. 500 m depth at about 35°C and 40 bar. The aim is to permanently bind CO2 into carbonates upon water-rock interaction. In order to evaluate the hydro-geochemical patterns and proportions of CO2 mineralization in the aquifer, full scale monitoring is needed. This will involve monitoring of conservative and gas tracers injected with the carbonated fluid, isotope ratios and major and trace elemental chemistry. A crucial issue of the monitoring is the quality of the sampling at depth and under pressure. Commonly, gas bubbles are observed when using commercial downhole samplers (bailers) and in order to avoid this problem, a piston-type downhole bailer was designed, constructed and tested as part of the project.